INFLUENCE OF CRYSTAL HYDRATE WATER ON THE PRODUCTS OF HEAT TREATMENT OF MAGNESIUM-MANGANESE(II) DIHYDROGENPHOSPHATES - Антрапцева, Надежда; Филькин, Игорь (SWorldJournal, 2020)
It is determined that during heat treatment of tetrahydrates Мg1-xМnx(Н2РО4)2•4Н2О crystal hydrate water effects on the changes in the quantitative composition of products and the characteristics of the process as a whole. The maximum amount of free mono